City Making And Mending In The United States: On Capitalizing a Social Environment - Lampard, Eric (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1980)
This paper surveys attitudes toward city building from the foundation of cities in colonial America to the present day in the United States. It treats the activity of city making and mending in terms of modal behaviour and institutions, not the iconography of cities nor their reputation among prominent intellectuals. It is ultimately concerned with whether capitalized social change tends to render the forms of urban society obsolete much as "progress" outmoded rural society in the late nineteenth and early twentieth centuries.